Attitudes about donor information differ greatly between IVF couples using their own gametes and those receiving or donating oocytes or sperm - Svanberg, Agneta Skoog (J Assist Reprod Genet, 2016)
OBJECTIVE: The objective of the study is to examine attitudes towards aspects of donation treatment based on a national Swedish sample of gamete donors and couples undergoing assisted reproductive techniques (ART). METHODS: The present study was part of the Swedish study on gamete donation, a prospective longitudinal cohort study including all fertility clinics performing gamete donation in Sweden. The sample comprised 164 oocyte donors, 89 sperm donors, 251 people treated with their own gametes (in vitro fertilisation (IVF)), 213 oocyte recipients and 487 sperm recipients. A study-specific questionnaire was used. RESULTS: Attitudes vary widely between couples using their own gametes for IVF and those receiving or donating oocyte or sperm. The groups differed in their responses to most questions. Oocyte and sperm donors were more likely to agree with the statements “The donor should be informed if the donation results in a child” and “Offspring should receive some information about the donor during mature adolescence” than recipients of donated gametes and couples treated with their own gametes. CONCLUSION: Donor recipients, IVF couples and donors expressed different attitudes towards openness and information when it came to gamete donation, and those differences seemed to depend on their current reproductive situation.